2012
DOI: 10.1128/jvi.01495-12
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Induces Telomerase Activity in Monocyte-Derived Macrophages, Possibly Safeguarding One of Its Reservoirs

Abstract: Monocyte-derived macrophages (MDM) are widely distributed in all tissues and organs, including the central nervous system, where they represent the main part of HIV-infected cells. In contrast to activated CD4 + T lymphocytes, MDM are resistant to cytopathic effects and survive HIV infection for a long period of time. The molecular mechanisms of how HIV is able to persist in macrophages are not fully elucidated yet. In this context, we have studied the effect of in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 81 publications
1
38
0
Order By: Relevance
“…[69][70][71][72] In the case of latently infected cells, the modulation of DDR by HIV-1 may involve viral proteins expressed at a very low level (e.g. reservoirs established in macrophages).…”
Section: Discussionmentioning
confidence: 99%
“…[69][70][71][72] In the case of latently infected cells, the modulation of DDR by HIV-1 may involve viral proteins expressed at a very low level (e.g. reservoirs established in macrophages).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HIV-1 envelope glycoprotein has been shown to disrupt Fas and TNF-related apoptosis-inducing ligand (TRAIL)-mediated apoptosis and regulate the induction of the prosurvival cytokine macrophage colony-stimulating factor (M-CSF) (52), whereas HIV Nef has been shown to prevent apoptosis in macrophages by inactivating the proapoptotic Bad protein (53). Others have shown that HIV infection induces noncanonical telomerase activity in macrophages that protects them from oxidative stress and DNA damage (54). Another study showed that SIV-specific CD8 ϩ T cells were unable to suppress viral replication in SIV-infected macrophages (55).…”
Section: The Gut Macrophage Reservoir In Hiv Infectionmentioning
confidence: 99%
“…The nondividing status of terminally differentiated macrophages and low deoxynucleoside triphosphate (dNTP) levels have to be accommodated in order for primate lentiviruses to establish a productive infection (5,6). Additionally, macrophages are resistant to the cytopathic effects of viral replication in comparison to the sensitivity of activated CD4 ϩ T cells (2,(7)(8)(9), and HIV-1 has evolved mechanisms to prolong the life span of infected macrophages (9,10). HIV-1 can also be detected in individuals on suppressive antiretroviral therapy (ART), raising the possibility that these cells serve as a viral reservoir (11).…”
mentioning
confidence: 99%